STUDY ON MICROBIAL CONTAMINATION OF MOBILE PHONES AND THEIR ROLE IN NOSOCOMIAL INFECTIONS IN A TERTIARY HOSPITAL OF SOUTH INDIA - Bhumbla, Upasana; Ahmad, Safaa Muneer; Mathur, Dinesh Raj; Bandey, Lubna; Mathur, Gyaneshwari (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Introduction: Mobile phones have become an essential accessory of our life in todays’ world.. The study revealed the potential role of mobile phones in nosocomial infections. Objectives: To screen the mobile phones of health-care personnel for microbial contamination in hospital. Methods: A total of 100 swabs were collected from mobile phones of 40 resident doctors and 10 health-care personnel before and after use of disinfectant. Samples were processed, and identification was done as per standard laboratory procedures. Results: Results revealed 92% bacterial contamination with monomicrobial or polymicrobial growth. Coagulase negative Staphylococci (29.59%) was the most predominant organism followed by Diphtheroids (22.44%). Other bacteria which were isolated Staphylococcus aureus, Micrococci, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Citrobacter spp. fungal growth included Aspergillus niger and Candida albicans. On the other hand, after using disinfectant, the contamination rate was reduced. Conclusion: Mobile phones act as a carrier for transmission of both community acquired as well as hospital acquired infections. However, with the proper use of disinfectants, and proper hand hygiene practices it can be reduced. Keywords: CONS(Coagulase-negative Staphylococci), S.aureus (Staphylococcus aureus), K.pneumoniae(Klebsiella pneumoniae).